Uganda - Integrating Gender into Policy Actions - Canagarajah, Roy S. (World Bank, Washington, DC, 2012)
The findings of both macro- and microeconomic analysis of the links between growth and gender inequality have shown that large gender disparities in basic human rights, resources, economic opportunity, and in political voice is directly and indirectly limiting growth in sub-Saharan Africa, and that women and girls are bearing the largest and most direct costs of these inequalities.